Application Of The Multiplex Polymerase Chain Reaction (M-PCR) For The Screening Of Vibrio Spp. From Rivers In Kuching, Sarawak - Vincent, Mickey; Tuah, Lawrance; Chan Sien Wei, Christy; Maurice Bilung, Lesley; Apun, Kasing (Borneo Journal of Resource Science and Technology, 2016)
The present study was conducted to investigate the occurrence of Vibrio spp. from selected rivers in Kuching, Sarawak (Malaysia) using Multiplex Polymerase Chain Reaction (m-PCR). During the 6-month study period, 19 samples were collected monthly from 7 rivers, followed by simultaneous detection of three Vibrio spp., Vibrio parahaemolyticus, Vibrio cholerae and Vibrio vulnificus, in a single tube PCR reaction. Three sets of primers targeting the thermolabile (tl), outer membrane protein (ompW) and hemolysin/cytolysin genes (vulCulsl) of V. parahaemolyticus, V. cholerae and V. vulnificus, respectively, were used. The results indicated that V. parahaemolyticus was the predominant species, occurring approximately 60.9% throughout the sampling period, followed by V. cholerae (23.1%) and V. vulnificus (16.0%). The months of July and December were found to be the months where all three Vibrio spp. were found to be at higher frequencies in the river samples. Results analyzed also indicated that the rivers with the highest prevalence of the three Vibrio spp. were Tambak Sejingkat, followed by Sungai Jernang and Sungai Tabuan. We conclude that m-PCR is a powerful and useful tool for the rapid and simultaneous detection of V. parahaemolyticus, V. cholerae and V. vulnificus from the riverine environments without the need for isolation and culturing. Furthermore, this method is highly specific, and could be applied in diagnostic laboratories for larger scale epidemiological investigations of Vibrio spp.